Basin analysis of Cretaceous to Tertiary selected wells in Kirkuk and Bai Hassan Oil Fields, Kirkuk, Northern Iraq - S.Al-Sheikhly, Saad; Y.Tamar-Agha, Mazin; M. Mahdi, Maher (Iraqi Journal of Science, 2023)
Basin analysis (geohistory) is carried out on the Cretaceous to Tertiary succession in five wells at Kirkuk and Bai Hassan Oil Fields during the Aptian to the Recent. The Foothill Zone exhibited a complex subsidence and uplift history over a period of about 132 Ma. The results from studied wells backstripping provide a record of the subsidence and uplift history in a number of important Meso-Cenozoic depositional successions. They show that there are three distinct episodes separated by unconformity surfaces. The value of compaction varies from large during the Cretaceous period to less clearly during the Paleogene and then almost non-existent during the Neogene. Generally, the subsidence is continuous and gradual during Mesozoic and suddenly increases in Cenozoic with obvious effect to the tectonic movements.